THE ROLE OF PRACTICAL TRAINING IN TEACHING STUDENTS TO LOGICAL THINKING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on reforms in public education, traditional and non-traditional education, and the role of practical training in teaching students to think logically through cognitive learning. And examples are given.